Force, flatness and touch without feeling: Thinking historically about haptics and buttons. (October 2017) - Plotnick, Rachel
In recent years, concerns have cropped up about the disappearance of analog buttons in favor of flat, slick touchscreens that ask little from their users' fingers beyond swipes, touches, and taps. This form of interfacing has generated concerns both about usability and about how users relate tactilely and affectively with digital media. This article suggests that worries about these discursive and material shifts related to finger force and flat design continue a conversation begun >100 years ago when the very concept of a "button" was new. Stitching together past and present, this study identifies a persistent struggle to make sense of how humans touch and feel machines, with questions about user agency, labor, individuality, and authentic engagement coming to the fore. Additionally, it makes a case for encouraging scholars to work at the intersection of history and haptic media systems.